Optimization of copper oxide film by dip coating technique for oxygen detection - Raship, Nur Amaliyana (2018)
Copper oxide (CuO) based gas sensor has been widely investigated due to its low- cost material, nontoxicity and abundant on earth. The CuO hierarchical structure is used to enhance the sensing performance of the gas sensor. This is because of its structure provides large surface area for the adsorption of gas into the sensing surface. However, most of the structure of CuO based gas sensors fabricated using various deposition techniques are particle structure. In this research, dip coating technique is proposed for the preparation of CuO hierarchical structure by optimized the annealing temperature, various pH of solutions and withdrawal speed of dip coating. The phase structure, morphology and surface roughness of CuO films were characterized by using X-ray diffraction (XRD), field emission scanning electron microscope (FESEM) and atomic force microscope (AFM), respectively. In addition, the thickness and electrical properties of CuO films were measured using surface profiler and four-point probe, respectively. Based on the results, 400 oC annealing temperature, pH 12.0 of CuO solution and 70 mm/min of withdrawal speed are the optimum parameters of CuO films for gas detection. The XRD results showed that these films have high crystal quality which crystallize along the (002) and (111) phase with preferential orientation along the c-axis of the CuO monoclinic structure. These films exhibit a uniform and homogeneous flower-like structure. The surface roughness of these films were 70.18 nm and the films thickness were found to be 0.76 μm. The electrical properties of these films show that they are conductive due to their lower resistivity which are 1.18 Ω.cm. Finally, these films were deposited at different withdrawal speed and their gas sensing ability towards oxygen gas were tested. As a result, CuO film at 70 mm/min of withdrawal speed exhibit sensitivity, response time and recovery time of 26.7 %, 2.381 s and 7.128 s, respectively. This research concludes that the CuO flower-like structure deposited by dip coating technique exhibit a good performance and works well as oxygen gas detection at room temperature.